Refusal to drunkenness test on the basis of the right against self-incrimination (2015)
The deaths and injuries caused by individuals under the influence of alcohol or other substances is subject of great worry amongst the varying legal systems, which have decided to take punitive measures through penal and administrative law to mitígate the